(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper explores the role of theoretical information in literary education as a key means of understanding the content of a literary text. It emphasizes the importance of a theoretical approach to literature that aids students in comprehending the deeper meaning of a text, considering its historical, cultural, and philosophical contexts. The article discusses various literary analysis methods, essential theoretical concepts used in text interpretation, and the methodology of literary studies. It also highlights the necessity of theoretical knowledge in literary interpretation and the pedagogical approaches used in literary education. The paper further investigates the practical application of theoretical knowledge in teaching literature and the vital role literary studies play in the educational process.